Konsep Pendidikan dan Proses Belajar Perspektif Ibn Qayyim Al-Jawziyyah Analisis Terhadap Metode Tarbiyah dalam Islam - Mutia Isfah Ardilah; Rosalina Zulhijjah; Ali Maulida (Ikatan Dai Indonesia, 2026)
This study aims to analyze the concept of education and the learning process from the perspective of Ibn Qayyim al-Jawziyyah and its relevance to contemporary Islamic education. This research employs a library research method with a descriptive-analytical approach to Ibn Qayyim's primary works and relevant secondary sources. The findings indicate that education, according to Ibn Qayyim, is inherently holistic, encompassing not only the acquisition of knowledge but also the cultivation of human fitrah, the strengthening of faith, the development of moral character, and the balanced growth of both physical and spiritual dimensions. The learning process is conceptualized as a gradual formation of personality aligned with stages of human development, beginning from the preconception phase to maturity (baligh). In educational practice, Ibn Qayyim emphasizes several key methods, namely habituation, role modeling, counseling (advice), educative punishment, and learning by doing. These findings highlight the strong relevance of Ibn Qayyim's educational thought in addressing contemporary challenges, particularly in strengthening character education, contextual learning, and the cultivation of adab within modern Islamic institutions. Therefore, his educational framework offers a significant theoretical foundation for developing an integrative, humanistic, and value-oriented model of Islamic education.